Effect of prior cues on action anticipation in soccer goalkeepers - Wang, Y.; Ji, Q.; Zhou, C. (Psychology of Sport and Exercise, 2019)
Objectives: Visual kinematic information is crucial to successful action anticipation in professional athletes. Here, we examined whether nonkinematic prior cues would influence the anticipatory judgment of penalty kicks and explored the neural correlates underlying expert advantage. Method: In the cue-anticipation task, congruency was manipulated such that the direction of a prior cue (directional arrow) was either congruent (i.e., same direction) or incongruent (i.e., opposite direction) with the subsequent direction of the penalty kick. Both behavioral performance and event-related potential activity elicited by cues and kicks were compared between expert goalkeepers and novices. Results: Action anticipation performance was increased in the congruent condition and was decreased in the incongruent condition. Expert goalkeepers outperformed novices both when the prior cue provided no directional information (neutral condition) and when it provided directional information incongruent, but not congruent, with the subsequent kick. Event-related potential activity analyses showed N1 and N2 amplitudes elicited by the kicks for the incongruent condition were larger than those for the congruent and neutral conditions only for expert goalkeepers. No significant difference was detected between experts and novices in the amplitude of the contingent negative variation elicited by the cues. Conclusions: In addition to the contribution of visual kinematic body information on action anticipation, prior cues significantly influenced predictions of action outcome. Expert advantage of action anticipation may be associated with proficient modulation of brain activity in early attention processing and conflict monitoring during the integration of these two kinds of information.